Wheat powdery mildew resistance: from gene identification to immunity deployment - Zou, Shenghao; Xu, Yang; Li, Qianqian; Wei, Yali; Zhang, Youlian; Tang, Dingzhong (Frontiers in Plant Science, 2023)
Powdery mildew is one of the most devastating diseases on wheat and is caused by the obligate biotrophic phytopathogen Blumeria graminis f. sp. tritici (Bgt).Due to the complexity of the large genome of wheat and its close relatives, the identification of powdery mildew resistance genes had been hampered for a long time until recent progress in large-scale sequencing, genomics, and rapid gene isolation techniques. Here, we describe and summarize the current advances in wheat powdery mildew resistance, emphasizing the most recent discoveries about the identification of genes conferring powdery mildew resistance and the similarity, diversity and molecular function of those genes. Multilayered resistance to powdery mildew in wheat could be used for counteracting Bgt, including durable, broad spectrum but partial resistance, as well as race-specific and mostly complete resistance mediated by nucleotide-binding and leucine rich repeat domain (NLR) proteins. In addition to the above mentioned layers, manipulation of susceptibility (S) and negative regulator genes may represent another layer that can be used for durable and broad-spectrum resistance in wheat. We propose that it is promising to develop effective and durable strategies to combat powdery mildew in wheat by simultaneous deployment of multilayered immunity.